Nehari method for locally Lipschitz functionals with examples in problems in the space of bounded variation functions - Figueiredo, Giovany M. (2018)
In this work we prove some abstract results about the existence of a minimizer for locally Lipschitz functionals, over a set which has its definition inspired in the Nehari manifold. As applications we present a result of existence of ground state bounded variation solutions of problems involving the 1-laplacian and the 1-biharmonic operator, where the nonlinearity satisfies mild assumptions.